Development of a Procedure for the Identification of Pharmaceutical Substance «Buserelin Acetate» by NMR Spectroscopy without Using Pharmacopoeia Reference Standard - N. E. Kuzmina; S. V. Moiseev; V. I. Krylov; V. A. Yashkir; V. A. Merkulov (Антибиотики и Химиотерапия)
The identification of the buserelin acetate sample was carried out without using the pharmacopeia reference standard. The identification was based on the spectral NMR data (1H,13C,1H-1H gCOSY,1H-13C gHSQC,1H-13C gHMBC) complex analysis. NMR experiment parameters were determined for the obtaining of spectra with S/N ratio above 50: 1 (1H) and 10:1 (13C). The inexpediency of using the acetate anion signal for calibration of the scale of chemical shifts in the spectra of an aqueous solution of buserelin acetate is shown. The assumption about the effect of the speed of prototropic tautomerism on the disappearance of signals of carbon atoms in positions 4 and 5 of the imidazole ring in the L-histidine fragment of buserelin acetate was made.